ABU HAMID MUHAMMAD AL-GHAZALI DAN METODE IJTIHADNYA DALAM AL-MUSTASHFA (Mazahib, 2007)
Al-Ghazali (1058 H/1111 M) is one of the prominent Islamic scholars who lived during the golden age. Due to his great contribution, al-Ghazali’s thoughts have been studied for centuries and deemed to be an important Islamic legacy. Al-Ghazali’s eminence in Islamic history can be seen from the title given to him, i.e. hujjatul Islam (the great defender of Islam) and the classical status of his work ‘al-Mustasyfa’, a book of Islamic juriprudence theory. He based his thought on three major Islamic sources: al-Qur’an, the Sunnah, and sound mind. This then have been employed in his discussion on the argumentation of ijma’.